F(5)=-2x+3

Simple and best practice solution for F(5)=-2x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(5)=-2x+3 equation:


Simplifying
F(5) = -2x + 3

Reorder the terms for easier multiplication:
5F = -2x + 3

Reorder the terms:
5F = 3 + -2x

Solving
5F = 3 + -2x

Solving for variable 'F'.

Move all terms containing F to the left, all other terms to the right.

Divide each side by '5'.
F = 0.6 + -0.4x

Simplifying
F = 0.6 + -0.4x

See similar equations:

| 9x^2-61x+4=0 | | 3-4x/5=-9 | | 5(3r-1)-(r-1)=1+5+3r-5 | | -2v+10= | | -(1+7v)-7v=111 | | 9=2-5x | | 1/3(5/3) | | 2x^4+x^2+5x+12=0 | | 3(x-5)+x=4(x-4)+1 | | -10x-12=-2-4(3x+8) | | 1x+25=7x+15 | | -2(7-x)+4=-4 | | 5b+6=b+14 | | 5/5-(5-5)= | | 3(x+2)=2(4x-3) | | 2=10(x+9)+6x | | 5x-22/6+x/30=x/5-1 | | 62.9296(y-100)+64.9278=63.546 | | 3x+5-40=125 | | 9c^2-4c^2+2c^2= | | 1/3(-5) | | 46-x=27 | | 4/21+1/7= | | 2(7-x)+4=-4 | | -6(x-5)=50-2x | | 5/5+6-z/2= | | 9-3m+mn-3n= | | 62.9296(100-y)+64.9278=63.546 | | -8x-9=23 | | 8t=7t+2/3 | | -11-4t=6+3(11-3t) | | 2x^2-5+167=0 |

Equations solver categories